Construction of a Microfluidic Platform With Core-Shell CdSSe@ZnS Quantum Dot-Encoded Superparamagnetic Iron Oxide Microspheres for Screening and Locating Matrix Metalloproteinase-2 Inhibitors From Fruits of Rosa roxburghii - Tao, Yi; Pan, Meiling; Zhu, Fei; Liu, Qing; Wang, Ping (Frontiers in Nutrition, 2022)
The microfluidic platform is a versatile tool for screening and locating bioactive molecules from functional foods. Here, a layer-by-layer assembly approach was used to fabricate core-shell CdSSe@ZnS quantum dot encoded superparamagnetic iron oxide microspheres, which served as a carrier for matrix metalloproteinase-2. The matrix metalloproteinase-2 camouflaged magnetic microspheres was further incorporated into a homemade microfluidic platform and incubated with extracts of fruits of Rosa roxburghii. The flow rate of the microfluidic platform was tuned. The major influencing parameters on ligand binding, such as dissociate solvents, incubation pH, ion strength, temperature, and incubation time were also optimized by using ellagic acid as a model compound. The specific binding ligands were sent for structure elucidation by mass spectrometry. The absolute recovery of ellagic acid ranged from 101.14 to 102.40% in the extract of R. roxburghii under the optimal extraction conditions. The linearity was pretty well in the range of 0.009–1.00 mg·ml−1 (R2 = 0.9995). The limit of detection was 0.003 mg·ml−1. The relative SDs of within-day and between-day precision were <1.91%. A total of thirteen ligands were screened out from fruits of R. roxburghii, which were validated for their inhibitory effect by enzyme assay. Of note, eleven new matrix metalloproteinase-2 inhibitors were identified, which may account for the antitumor effect of fruits of R. roxburghii.